TEACHING PART OF SPEECH TO EFL STUDENTS THROUGH â€œTHE TORTOISE AND THE HAREâ€ STORY - Fitri Apriyanti (Ed-Humanistics : Jurnal Ilmu Pendidikan, 2020)
This research is intended to make learners using the correct part of speech in the correct position in the sentence. The research method used to teaching part of speech through a story is descriptive method by reading, finding, identifying, classifying and writing about the part of speech related to the story. The participants of this research are the students of one of university in Jakarta. The results of this research are: there are 17 nouns, 33 verbs, 18 adjectives, 11 adverbs, 9 pronouns, 11 prepositions, 5 conjunctions and 1 interjection. Keywords: Teaching, Speech, Tortoise, Hare